The administration of the Badilis districts according to the two state authorities for the year 1316 AH / 1898 CE and 1318 AH / 1900 CE - Yunus, Majed (Humanities Journal of University of Zakho, 2020)
Bitlis was the center of a strong Kurdish emirate in northern Kurdistan, southeastern Anatoliafor many centuries. Bitlis played a very important role in different aspects of Kurdish life, representing significant political, military and economic equations between two vast and powerful states, the Ottoman Empire and the Safavid State. One of these roles associated with Bitlis’ geographical position, whichwas militarily fortified and as being close to the bordersof the two mentionedcountries. Such position led to make the two forces be wooed on Bitlis. Hence, the Ottomans were feared of losing Bitlis, joining the Safavids. They, in turn, took advantage of the opportunities to attract the attention of the Bitlis people. So, this positively affected the economic life of the emirate in various ways. At that time, and having the crisis between the Ottomans and the Safavids, Bitlis leaders had to maintain a balance between them as much as possible in order to preserve their survival. However, the Ottomans resorted to violence and sought excuses to overthrow the emirate, to at least weaken it, and put an end to its continued growth, which was prevailing during the establishment of treaties between the two forces. Bitlis continued to live amid those circumstances until the Ottomans controlled it at the end of the first half of the 19th century. The Ottomans then changed their administrative boundaries to some extent, forming a new mandate that included a number of sanjaks and districts. In the current paper, all the administrative aspects of the Bitlis districts will be addressedaccording to the Salnama in1898 and 1900. These districts included Akhlat. (Khalat), Khaizan, Mottaki (Motki), Bolang, Arto (Wartu), Malazcard, Sasson, Ghazan, Arwa (Arukh), Sherwan, Barwari, Qalb, and Jabakjour separately. The study also tackled the government departments that existed at the time, identifying the administrative staff in each administration such as qaemakamat, courts, tax authorities, the civil status, banks, finance, land registry (tabu), telegraph, police departments, public debt, civil and military schools, municipalities, knowledge departments, security, the committees of military media, prisons, the departments of agriculture and agricultural products and other things related to each district. All these reflect important aspects of the administrative history of Kurdistan during the last era of the age of the Ottoman Empire.